Design and development of tire nut removal - Nor Syazwani, Hamsan (2013)
This thesis presented about design and development of tire nut removal based on pitch circle diameter (PCD) 114mm car. Based on the existing model, there have a few improvements to be done. First thing is to reduce the weight of the tire nut removalwhere appropriate by designing more compact and smaller size of mechanism of tire nut removal but still in PCD 114mm. Secondly, this study also conduct to utilize lessexpensive materials and production costs in order to access this tire nuts removal intomarket. Corresponds to the project background and problem statements, it is decided that the objectives of the project are to design, fabricate and assemble the tire nut removal with lighter weight compared with the current design, to utilize less expensivematerials and production cost and to design a lower input torque and find the suitable gear system complete with suitable actuator that fulfils the required specification. Studywas focused on restructure the tire nuts removal in increasing the torque and produceshigh speed and select the best option which is capable to be fabricated at UMP. Threedifferent types of gear mechanism have been designed by using Geartrax 2003 andSolidwork 2012. Then, analysed the gear mechanism by Finite Element Analysis: Algor23.0 software. Three parameters have been set up in choosing the best tire nuts removal to be fabricated which are the weight of tire nuts removal, the torque and speed of tirenuts removal, and the production cost of tire nuts removal.